2022
DOI: 10.1111/pbi.13774
|View full text |Cite
|
Sign up to set email alerts
|

PhieABEs: a PAM‐less/free high‐efficiency adenine base editor toolbox with wide target scope in plants

Abstract: Summary Adenine base editors (ABEs), which are generally engineered adenosine deaminases and Cas variants, introduce site‐specific A‐to‐G mutations for agronomic trait improvement. However, notably varying editing efficiencies, restrictive requirements for protospacer‐adjacent motifs (PAMs) and a narrow editing window greatly limit their application. Here, we developed a robust high‐efficiency ABE (PhieABE) toolbox for plants by fusing an evolved, highly active form of the adenosine deaminase TadA8e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 37 publications
1
36
0
1
Order By: Relevance
“…A single-stranded DNA-binding domain from Rad51 protein (RAD51-DBD) was inserted between the deaminases and nCas9, which was reported to substantially increase activity and an expand editing window of CBE ( Zhang et al, 2020 ). Tan et al (2022) recently reported that RAD51-DBD can also dramatically increase editing efficiency of ABE. This CBE system contains a CsU6-tRNA-gRNA-scaffold unit for multiplex editing.…”
Section: Resultsmentioning
confidence: 99%
“…A single-stranded DNA-binding domain from Rad51 protein (RAD51-DBD) was inserted between the deaminases and nCas9, which was reported to substantially increase activity and an expand editing window of CBE ( Zhang et al, 2020 ). Tan et al (2022) recently reported that RAD51-DBD can also dramatically increase editing efficiency of ABE. This CBE system contains a CsU6-tRNA-gRNA-scaffold unit for multiplex editing.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the addition of the human Rad51 DBD to ABE systems produced diverse results in editing efficiency when fused to different Cas9 variants ( Tan et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…A single-stranded DNA-binding domain from Rad51 protein (RAD51-DBD) was inserted between the deaminases and nCas9, which was reported to substantially increase activity and an expand editing window of CBE (Zhang et al, 2020). Tan et al recently reported that RAD51-DBD can also dramatically increase editing efficiency of ABE (Tan et al, 2022). This CBE system contains a CsU6-tRNA-gRNA-scaffold unit for multiplex editing.…”
Section: Developing a Cbe For Citrusmentioning
confidence: 99%